Utilização de medicamentos por pacientes portadores da doença de Alzheimer atendido em ambulatório de hospital universitário - Lima, Carlos Eduardo Pereira (2008)
BACKGROUND: Alzheimer's disease (AD) is a degenerative disease of known etiology in part, with aspects neuropathological and neurochemical features. Your pharmacological treatment is done with cholinesterase inhibitors alone or combined with memantine. OBJECTIVE: To describe the conditions of use of medicines by patients with AD treated at the Center for the Elderly (CAI) of Hospital Universitário Walter Cantidio (HUWC), Federal University of Ceará (UFC). METHOD: This is an observational, descriptive, cross, developed in the Outpatient Pharmacy HUWC. The study population is accompanied by the CAI, which interviewed 200 caregivers and / or guardians of patients with AD. The interviews were conducted-between the months of May/2007 and February/2008, using as an instrument of data collection a questionnaire with opened and closed questions. Were observed in the study the socio-demographic characteristics of patients, the characteristics of medication use and comorbidities, as well as pharmaceutical aspects of drug utilization. RESULTS: From 200 patients in the study, one can observe that 73% of patients were women, average age was 80 years. About 90% of patients lived in Fortaleza, 45.5% were under 4 years of schooling and 35,5% had family income between 1 to 2 minimum wages, and retirement as the main source of income. Regarding marital status, 48% were widows living mostly with children and grandchildren. Regarding the use of drugs, 77% of the patients were only prescribed by a physician, an average of 6 medications per patient, where the predominant use of drugs that act on the central nervous system. As for specific dmgs for AD, 78% of the population under study made use of Rivastigmine, 47.5% of caregivers reported the possible side effects of drug therapy for specific AD and 57% reported improvement in health status of patients after early treatment in CAI. Of the patients studied, 95% had other (s) problem (s) in addition to the health of, primarily related to the cardiovascular system. The activities related to non- pharmacological treatment of AD, 56% of patients performed some type of activity, with a prevalence of physical activity formal. Among the survey respondents, 82% made mistakes related to aspects of conservation and use of dmgs for specific therapy in AD. CONCLUSION: In this study we observed that most patients with AD seen at CAI are low- income elderly and had a high prevalence of possible adverse reactions and other comorbidities, so adding the concomitant use of more medications, and may cause other adverse reactions and also drug interactions. The use of dmgs by the elderly should be evaluated seeking to achieve maximum therapeutic effects and avoid problems related to the irrational use of medicines. Thus, it becomes increasingly evident the need for Pharmacotherapeutic Follow-up to minimize the related problems.